Effect of precipitation of silicone oil-based nanofluid on thermal conductivity. (16th April 2022) - Lee, Duk Hyung; Kim, Dong-Hyun; Choi, Yeon Suk
This study investigated the effect of the precipitation of nanofluid additives on thermal conductivity in various environments using a bidirectional 3 omega (3ω) method. Silicone oils with viscosities of 50, 500, and 1000 CS were used as the base fluid. Nanoparticles containing aluminium spheres of 100 nm diameter were added to the base fluid at a mass ratio of 0.5%. The experimental set-up was designed and fabricated, and the bidirectional 3ω method was verified by measuring the thermal conductivity of the well-known liquid. Using the nanofluids, thermal conductivities were measured at various temperatures and viscosities. The measurement results are discussed with respect to the elapsed time of precipitation. In addition, the effect of penetration depth on the thermal conductivity is investigated.